Mitigating counterparty risk - Yalin Gündüz (Deutsche Bundesbank, 2018)
This paper provides initial evidence on counterparty risk-mitigation activities of financial institutions on the basis of Depository Trust and Clearing Corporation's (DTCC) proprietary bilateral credit default swap transactions and positions. We show that financial institutions that are active buyers of protection from a specific counterparty undertake successive contracts and purchase protection written on them, even avoiding wrong-way risk mitigation. Higher stock return and CDS price volatility, lower past stock returns, and higher CDS prices of the counterparty are shown to have an increasing effect on the hedging behaviour against the counterparty. As the current regulatory frameworks explicitly formulate any protection purchase on the counterparty would diminish the required capital, this type of risk mitigation could follow regulatory capital relief motives and provides a viable hedging instrument beyond receiving coverage through collateral.
Keywords: G11; G21; G23; 330; credit default swaps; DTCC; OTC markets; hedging; Basel III; CRR